47.1k views
7 votes
Parallelograms don’t understand

Parallelograms don’t understand-example-1

1 Answer

9 votes

Answer:-43 + 9x = 0

Step-by-step explanation:Simplifying

9x + -43 = 0

Reorder the terms:

-43 + 9x = 0

Solving

-43 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '43' to each side of the equation.

-43 + 43 + 9x = 0 + 43

Combine like terms: -43 + 43 = 0

0 + 9x = 0 + 43

9x = 0 + 43

Combine like terms: 0 + 43 = 43

9x = 43

Divide each side by '9'.

x = 4.777777778

Simplifying

x = 4.777777778

User Alexanderjslin
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.